Children Empowerment in C.S. Lewis’ Novel “The Lion, The Witch And The Wardrobe” - Adi Irma Suryadi; Dariyana Dariyana (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
This research is aimed to describe Lucy’s thoughts, feelings, and actions in C.S. Lewis’s novel The Lion, the Witch, and the Wardrobe. The problem that formulated in the research will be answered based on Lucy’s thoughts, actions, and feelings and then describe it. The main source for this research was C.S. Lewis’s novel The Lion, the Witch, and the Wardrobe. This novel is considered as a children’s literature. The focus and the data for this research were events in the novel which showing Lucy’s thoughts, feelings, and actions. The data were analysed by using qualitative content analysis. The instrument was the researcher himself. There are four criteria: credibility, transferability, dependability, and confirmability, which the researcher used in order to make trustworthiness. The findings showed that this novel contains children’s empowerment. Children empowerments are considered as important aspects in children’s story and it has great influence to enrich children’s intelligence and emotion in their growing period, The Lion, the Witch and the Wardrobe can be categorized as a good novel.